Blood transcriptome responses to PFOA and GenX treatment in the marsupial biomedical model Monodelphis domestica - Cao, Wenqi; Horzmann, Katharine; Schemera, Bettina; Petrofski, Myra; Kendall, Trisha; Spooner, Jennifer; Rynders, Patricia E.; VandeBerg, John L.; Wang, Xu (Frontiers in Genetics, 2023)
Perfluoroalkyl and poly-fluoroalkyl substances (PFASs) are widely used in industrial and consumer products. Due to their environmental persistence and bioaccumulation, PFASs can be found in the blood of humans and wild animals all over the world. Various fluorinated alternatives such as GenX have been developed to replace the long-chain PFASs, but there is limited information about their potential toxicity. The current study developed blood culture protocols to assess the response to toxic compounds in the marsupial, Monodelphis domestica. After whole-blood culture conditions were tested and optimized, changes in gene expression in response to PFOA and GenX treatment were assessed. More than 10,000 genes were expressed in the blood transcriptomes with and without treatment. Both PFOA and GenX treatment led to significant changes in the whole blood culture transcriptomes. A total of 578 and 148 differentially expressed genes (DEGs) were detected in the PFOA and GenX treatment groups, 32 of which overlapped. Pathway enrichment analysis revealed that DEGs involved in developmental processes were upregulated after PFOA exposure, while those enriched for metabolic and immune system processes were downregulated. GenX exposure upregulated genes associated with fatty acid transport pathways and inflammatory processes, which is consistent with previous studies using rodent models. To our knowledge, this study is the first to investigate the effect of PFASs in a marsupial model. The findings provide supportive evidence for significant transcriptomic alterations, suggesting that this mammalian model may provide a mechanism for exploring the potential toxicity of PFOA and GenX.